The Complex Fibrinogen Interactions of the Staphylococcus aureus Coagulases - Thomas, Sheila; Liu, Wen; Arora, Srishtee; Ganesh, Vannakambodi; Ko, Ya-Ping; Höök, Magnus (Frontiers in Cellular and Infection Microbiology, 2019)
The two coagulases, von Willebrand factor binding protein (vWbp) and Coagulase (Coa), are critical virulence factors in several animal models of invasive Staphylococcus aureus (S. aureus) infections. These proteins are part of an intricate system of proteins that S. aureus uses to assemble a fibrinogen (Fg)/fibrin protective shield surrounding the microorganism. This shield allows the bacteria to evade clearance by the host phagocytic cells. The coagulases can non-proteolytically activate the zymogen prothrombin to convert Fg to fibrin and promote the Fg/fibrin shield formation. The coagulases also bind directly to Fg and the interaction between Coa and Fg has been previously characterized in some detail. However, the mechanism(s) by which vWbp interacts with Fg remains unclear. Here, we show that vWbp and Coa have distinct interactions with Fg, despite being structurally similar. Coa binds with a significantly higher affinity to soluble Fg than to Fg coated on a plastic surface, whereas vWbp demonstrates no preference between the two forms of Fg. The two coagulases appear to target different sites on Fg, as they do not compete with each other in binding to Fg. Similar to Coa, both the N- and C-terminal halves of vWbp (vWbp-N, vWbp-C, respectively) harbor Fg-binding activities. The higher affinity Fg-binding activity resides in vWbp-N; whereas, the C-terminal region of Coa encompasses the major Fg-binding activity. Peptides constituting the previously identified Coa/Efb1 Fg-binding motif fail to inhibit vWbp-C from binding to Fg, indicating that vWbp-C lacks a functional homolog to this motif. Interestingly, the N-terminal prothrombin-binding domains of both coagulases recognize the Fg β-chain, but they appear to interact with different sequence motifs in the host protein. Collectively, our data provide insight into the complex interactions between Fg and the S. aureus coagulases.